Ugly Betty - The Complete Third Season Episode 1-24 - Nelli, Victor jr; Spiller, Michael; Savage, Fred; Price, Michael A.; Ferrera, America; Mabius, Eric; Williams, Vanessa
It's a year of change for Betty and her friends at Mode. With the future of the magazine up in the air, a new roommate and the ever-changing carousel of office relationships spinning faster than ever, Betty's life is full of surprises. On top of it all, Betty's move to the big city has her wondering whether she truly belongs in her new fast-paced world. [Cover]